Digital Storytelling: A District Initiative for Academic Literacy Improvement. Issue 3 (3rd March 2019) - Vu, Viet; Warschauer, Mark; Yim, Soobin
Abstract: With young people increasingly learning and communicating through visual and social media, schools are looking for ways to tap into students' interest in digital media. In a school district in Southern California, a very promising approach to technology use has emerged that integrates digital storytelling into instruction. Findings from a first‐year exploratory study suggest that students who engage in digital storytelling develop their academic literacy and important technology and media arts skills. Yet, digital storytelling is being implemented very unevenly in the district, and teachers who wish to implement it face challenges in integrating it into a full curriculum. To achieve more consistent integration and better results, the researchers recommend that the district articulate the role of digital storytelling in district/state curricular goals and develop a framework for implementation consistent with this articulation.